Factors of Social Conditions on The Influence of Housing Distribution Patterns in Tasikmalaya City - Fuadah, Inayatul (Jurnal Pendidikan Ilmu Sosial, 2023)
Social interaction in each housing is formed by the closeness of the space between houses, so that the pattern of housing distribution allows for differences in social conditions. The purpose of this study is to analyze the social condition factor on the influence of housing distribution patterns in the City of Tasikmalaya. This study uses the method of multiple regression statistics with research variables, namely housing distribution patterns, population growth, population density, the ratio of accessibility support facilities, the ratio of health facilities, the ratio of educational facilities and the ratio of economic facilities. Based on the results of social conditions have an influence on the pattern of housing distribution. This study has a multiple regression coefficient between several variables, namely 0.744, which means that there is a correlation between all variables X simultaneously with variable Y. The threshold value of the coefficient is 0.5 so that if it is more than that, it has a strong correlation. A strong correlation is related to social condition variables, namely population, population density, accessibility, health facilities, educational facilities and economic facilities.